STRATEGI PEMASARAN, KUALITAS PELAYANAN, IDENTITAS MEREK TERHADAP LOYALITAS PELANGGAN PADA UMKM PULIH BOBA & COFFE - Hudaibi, Hudaibi (YHMM PUBLISHING, 2025)
The modern beverage industry in Indonesia, especially boba and coffee drinks, has grown rapidly, encouraging the expansion of Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector. MSMEs play a crucial role in supporting the national economy, creating jobs, and fostering local entrepreneurship. However, many MSMEs face challenges in sustaining their businesses. Marketing strategies are essential to adapt to market dynamics and remain competitive. This study focuses on Pulih Boba Drinks & Coffee, an emerging MSME, and analyzes the influence of marketing strategy, service quality, and brand identity on customer loyalty. Using a quantitative approach and descriptive method, data were collected through questionnaires from 100 active customers. The analysis shows that digital marketing, quality service, and strong brand identity have a significant and positive impact on customer loyalty, both partially and simultaneously. A total correlation value of 0.671 (p < 0.01) highlights the importance of an integrated approach in building long-term customer relationships.